President’s Message - Hollett, Sharon (Operating Room Nurses Association of Canada Journal, 2021)
How do you define a perioperative nurse? ORNAC’s current by-laws offer a definition in Section 1, 1.01(f). It reads as follows: “Canadian Perioperative Registered Nurse” means a registered nurse licensed to practice within a Canadian province or territory, whose field of practice is focused on the perioperative continuum of care providing safe and effective care/service to the surgical patient/client and their family. In addition, perioperative nursing practice focuses on but is not limited to education, leadership, research and advanced perioperative nursing practice in the settings of hospital operating rooms, ambulatory care settings/facilities, out-patient clinics, private/non-hospital surgical suites and physician offices, and educational institutions.”1